emm Types and clusters and macrolide resistance of pediatric group A streptococcal isolates in Central Greece during 2011-2017 - Grivea, Ioanna N. (PLoS One, 2020)
BACKGROUND: The surveillance of emm types and macrolide susceptibility of group A streptococcus (GAS) in various areas and time periods enhances the understanding of the epidemiology of GAS infections and may guide treatment strategies and the formulation of type-specific vaccines. Greece has emerged as a country with high macrolide use. However, studies suggest a gradual reduction in macrolide consumption after 2007. METHODS: During a 7-year period (2011–2017), 604 GAS isolates were recovered from consecutive children presenting with pharyngeal or nonpharyngeal infections in Central Greece; 517 viable isolates underwent molecular analysis, including emm typing. RESULTS: Isolates belonged to 20 different emm types (in decreasing order of prevalence: 1, 89, 4, 12, 28, 3, 75 and 6, accounting for 88.2% of total isolates). The emm types comprised 10 emm clusters (five most common clusters: E4, A-C3, E1, A-C4 and A-C5). The emm89 isolates were acapsular (‘new clade‘). Overall macrolide resistance rate was 15.4%, and cMLS(B) emerged as the predominant resistance phenotype (56.4%). The lowest annual resistance rates occurred in 2014 (13.1%), 2016 (5.5%) and 2017(8.0%) (P for trend = 0.002). Consumption of macrolide/lincosamide/streptogramin B declined by 22.6% during 2011–2017. Macrolide resistance and emm28 and emm77 types were associated (both P<0.001). The most frequently identified genetic lineages of macrolide-resistant GAS included emm28/ST52, emm77/ST63, emm12/ST36, emm89/ST101 and emm4/ST39. We estimated that 98.8% of the isolates belonged to emm types incorporated into a novel 30-valent M protein vaccine. CONCLUSIONS: In Central Greece during 2011–2017, the acapsular emm89 isolates comprised the second most prevalent type. Susceptibility testing and molecular analyses revealed decreasing GAS macrolide resistance rates, which may be attributed to the reduction in the consumption of macrolides and/or the reduced circulation of macrolide-resistant clones in recent years. Such data may provide valuable baseline information in targeting therapeutic intervention and the formulation of type-specific GAS vaccines.